2021
DOI: 10.24191/ajue.v17i4.16213
|View full text |Cite
|
Sign up to set email alerts
|

What's Missing? How Interpersonal Communication Changes During Online Learning

Abstract: During the Covid-19 pandemic in Indonesia, all communication activities have been carried out mostly through CMC, including online learning that students must experience. This situation brings big changes in the communication process between lecturers and students and vice versa. This paper aims to see how interpersonal communication changes in the online lecture process and what elements of interpersonal communication are lost with technology in online learning. The data collection method in this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Learner-content interaction is the capability to access and interact with information/content [ 9 ]. Interaction with students is one of the most important responsibilities of teachers, both in traditional curriculum and in online courses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Learner-content interaction is the capability to access and interact with information/content [ 9 ]. Interaction with students is one of the most important responsibilities of teachers, both in traditional curriculum and in online courses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the teacher gives a lecture and the students listen, sending and receiving messages occur, resulting in sufficient communication. Effective communication is undoubtedly dependent not only on messages but also on specific characteristics in which interpersonal communication can be effective [ 9 ]. Learner-learner interaction includes the interaction of learners with each other and the creation of a learning community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is widely accepted the assumption that through the use of technological means for communication, whether they are synchronous or asynchronous, some elements of nonverbal communication are lost to varying degrees. (Anzari & Pratiwi, 2021;Stodel, et. al.…”
Section: Communication Tools For Distance Educationmentioning
confidence: 99%
“…Chadha (2018) also found that online collaboration in courses could "enhanc[e] student deliberative performance" in politics courses and could further "be used to complement a variety of disciplines" (p. 1), in which, unlike face-to-face class environments, all students are required to participate in online environments, which means that students need to develop skills to collaborate productively with their peers despite their personal differences. Although online collaboration can have some advantages, such as flexibility, many dimensions of interpersonal communication may be missing in online classes, such as the loss of empathy between students due to the absence of face-to-face communication, which causes interpersonal communication not to work effectively (Putri Anzari & Pratiwi, 2021). For example, it may lead to some obstacles regarding interpersonal skills and relationships, given that instructors in online classes may feel that their connection with students is limited, without much energy transfer that happens more naturally in the face-to-face classroom, such as feeling less support because of the physical disconnection with the classmates and teachers; lack of a sense of community, body language or someone's energy (see Bazylak & Weiss, 2017;Davis et al, 2019;Pacansky-Brock, 2016).…”
Section: Working With Distributed Teamsmentioning
confidence: 99%